2017
DOI: 10.1021/acs.est.7b00693
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Soil Ecosystem Multifunctionality by Dissipating Manure-Induced Antibiotics and Resistance Genes

Abstract: The application of animal manure containing antibiotic residues to farmlands as an organic fertilizer causes a long-term potential threat to the ecological environment of farmland. This study analyzed the effects of abating typical antibiotics and resistance genes (ARGs) applied with pig manure on farmland soil as well as on soil ecosystem multifunctionality (EMF) and its influencing factor. The results showed that Lolium multiflorum exhibited significantly stronger abatement of typical antibiotics and ARGs wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Results from these analyses indicated that ryegrass roots affect the life strategies and interactions of fungi through their own direct and indirect effects on soil pH, trace elements, soil structures, and antibiotics. Biochar addition enhanced the positive effect of soil pH in deceasing antibiotic concentrations (p < 0.01), indicating that pH variation may promote the degradation of antibiotics (Liang et al, 2017). Liang et al (2017) found that a combination of biochar and ryegrass treatment mitigates the effects of antibiotics more effectively than with ryegrass planting alone.…”
Section: Alternative Mechanisms Influencing Fungal Life Strategies Anmentioning
confidence: 95%
See 3 more Smart Citations
“…Results from these analyses indicated that ryegrass roots affect the life strategies and interactions of fungi through their own direct and indirect effects on soil pH, trace elements, soil structures, and antibiotics. Biochar addition enhanced the positive effect of soil pH in deceasing antibiotic concentrations (p < 0.01), indicating that pH variation may promote the degradation of antibiotics (Liang et al, 2017). Liang et al (2017) found that a combination of biochar and ryegrass treatment mitigates the effects of antibiotics more effectively than with ryegrass planting alone.…”
Section: Alternative Mechanisms Influencing Fungal Life Strategies Anmentioning
confidence: 95%
“…Biochar addition enhanced the positive effect of soil pH in deceasing antibiotic concentrations (p < 0.01), indicating that pH variation may promote the degradation of antibiotics (Liang et al, 2017). Liang et al (2017) found that a combination of biochar and ryegrass treatment mitigates the effects of antibiotics more effectively than with ryegrass planting alone. Following these observation, the rapid mitigation of antibiotics in the RS + biochar treatment significantly enhanced fungal inter-specific relationships and increased the number of positive correlations among fungal taxa abundances.…”
Section: Alternative Mechanisms Influencing Fungal Life Strategies Anmentioning
confidence: 95%
See 2 more Smart Citations
“…3 Micro-levels of antibiotics in water do not usually cause acute toxicity; however, long-term exposure could lead to chronic toxicity for organisms in the environment. 4 In addition, widely-used antibiotics can induce the generation of antibiotic-resistant genes (ARGs) in microorganisms, [5][6][7] which can proliferate and widely disseminate in ecosystems, thereby posing a great danger to human health. 8 Experts have demonstrated that the emergence of "super bacteria" or "multi-drug resistant bacteria" may be associated with the environmental contamination of antibiotics and the killing of microbial communities.…”
Section: Introductionmentioning
confidence: 99%